Financial modeling for decision making : using MS-Excel in accounting and finance - Messer, Ron (Emerald Publishing Limited, 2020)
This book provides accounting students in post-secondary institutions with an advanced level understanding of how to use MS-Excel to make business decisions. It reflects real-life applications of this important analytical tool, which has become the accepted industry standard for spreadsheet software.- Resumé vydavatel
Includes index.
Keywords: účetní knihy; tabulkové procesory; podniky; účetnictví; finance; account books; electronic spreadsheets; business enterprises; accounting; elektronické knihy; příručky; electronic books; handbooks and manuals